Retrotransposons: How the continuous evolutionary front shapes plant genomes for response to heat stress - Papolu, Pradeep K.; Ramakrishnan, Muthusamy; Mullasseri, Sileesh; Kalendar, Ruslan; Wei, Qiang; Zou, Long−Hai; Ahmad, Zishan; Vinod, Kunnummal Kurungara; Yang, Ping; Zhou, Mingbing (Frontiers in Plant Science, 2022)
Long terminal repeat retrotransposons (LTR retrotransposons) are the most abundant group of mobile genetic elements in eukaryotic genomes and are essential in organizing genomic architecture and phenotypic variations. The diverse families of retrotransposons are related to retroviruses. As retrotransposable elements are dispersed and ubiquitous, their “copy-out and paste-in” life cycle of replicative transposition leads to new genome insertions without the excision of the original element. The overall structure of retrotransposons and the domains responsible for the various phases of their replication is highly conserved in all eukaryotes. The two major superfamilies of LTR retrotransposons, Ty1/Copia and Ty3/Gypsy, are distinguished and dispersed across the chromosomes of higher plants. Members of these superfamilies can increase in copy number and are often activated by various biotic and abiotic stresses due to retrotransposition bursts. LTR retrotransposons are important drivers of species diversity and exhibit great variety in structure, size, and mechanisms of transposition, making them important putative actors in genome evolution. Additionally, LTR retrotransposons influence the gene expression patterns of adjacent genes by modulating potential small interfering RNA (siRNA) and RNA-directed DNA methylation (RdDM) pathways. Furthermore, comparative and evolutionary analysis of the most important crop genome sequences and advanced technologies have elucidated the epigenetics and structural and functional modifications driven by LTR retrotransposon during speciation. However, mechanistic insights into LTR retrotransposons remain obscure in plant development due to a lack of advancement in high throughput technologies. In this review, we focus on the key role of LTR retrotransposons response in plants during heat stress, the role of centromeric LTR retrotransposons, and the role of LTR retrotransposon markers in genome expression and evolution.